PENINGKATAN KOGNITIF SISWA PADA PELAJARAN BIOLOGI MELALUI PENERAPAN MODEL DISCOVERY LEARNING DI KELAS XI IPA2 SMA NEGERI 1 ANGKOLA SELATAN - Erni Lubis (Universitas Negeri Medan, 2017)
Abstract: Cognitive Improvement of Students on Biology Lesson Through Application of Discovery Learning Model In Class XI IPA2 SMA Negeri 1 South Angkola. This study aims to improve students' cognitive learning outcomes by applying the Discovery Learning model. Subjects in this study amounted to 27 people. In the first cycle only 12 students got mastery learning, or the percentage of graduation by 37.03% with an average of 67.4 and not yet completed in a classical manner. In cycle II, 23 students got the complete value and left 4 students did not get the complete or complete value of 85.1% with an average of 82.96 which shows the complete individual and class. Data of psychomotor student learning result in cycle I are psychomotoric on data obtained (34,3%), data processing (33,3%) and conclusion (35,2%), while in cycle II, among others: psychomotor on data (69.4%), data processing (68.5%) and conclusions (71.3%). Keywords : Results of Cognitive Learning, Psychomotor Learning Outcomes, Discovery Learning Abstrak : Peningkatan Kognitif Siswa Pada Pelajaran Biologi Melalui Penerapan Model Discovery Learning Di Kelas XI IPA2 SMA Negeri 1 Angkola Selatan . Penelitian ini bertujuan untuk meningkatkan hasil belajar kognitif siswa dengan diterapkannya model Discovery Learning. Subjek dalam penelitian ini berjumlah 27 orang. Pada siklus I hanya 12 siswa mendapat ketuntasan belajar, atau persentasi kelulusan sebesar 37,03 % dengan rata-rata 67,4 dan belum tuntas secara klasikal. Pada siklus II, 23 siswa mendapat nilai tuntas dan menyisakan 4 orang siswa tidak mendapat nilai tuntas atau ketuntasan sebesar 85,1% dengan rata-rata 82,96 yang menunjukkan tuntas secara individu dan kelas. Data hasil belajar psikomotorik siswa pada siklus I antara lain: psikomotorik pada data yang diperoleh (34,3%), pengolahan data (33,3%) dan kesimpulan (35,2%), sedangkan pada siklus II antara lain: psikomotorik pada data yang diperoleh (69,4%), pengolahan data (68,5%) dan kesimpulan (71.3%). Kata Kunci : Hasil Belajar Kognitif, Hasil Belajar Psikomotorik, Discovery Learning